Analisis Komparatif Sistem Pemasaran Tandan Buah Segar Perkebunan Rakyat Bersertifikasi dan Non-Sertifikasi di Kelurahan Sorek Satu Kecamatan Pangkalan Kuraskabupaten Pelalawan - Nia Bonita Octaviani; Sakti Hutabarat; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The supply chain of FFB varies between RSPO-certified scheme smallholders and non-certified independent smallholders. Certification might be the main factors of the variation. The objective of this study are (1) to analyse marketing channels, marketing margin, marketing efficiency,and market structure of FFB; (2) to analyse elasticity of price transmission of certified FFB;  (3) to identify constraints in FFB marketing system; and (4) to evaluate the impacts of RSPO certification. The population of this study of RSPO-certified scheme smallholders (KKPA) and non-certified independen smallholders in Pangkalan Kuras District. The sample size are 82 farmers of RSPO-certified smallholders selected randomly and 76 farmers of non-certified smallholders chosen purposively. The study also select several marketing institutions using snowball method. The results show that the marketing channel I of the RSPO-certified smallholders is more efficient than the non-certified smallholders. The marketing chain of the RSPO-certified smallholder is the shortest chain. The market structure of RSPO-certified smallholders is monopsony while the non-certified smallholders tend to be oligopsony. The RSPO certification gives more access to the market with low impact on environment and social life.   Keywords: Marketing analysis, RSPO, scheme smallholders, independent